Elevated root-zone P and nutrient concentration do not increase yield or cannabinoids in medical cannabis - Hershkowitz, Julie A.; Westmoreland, F. Mitchell; Bugbee, Bruce (Frontiers in Plant Science, 2025)
Elevating nutrient input is thought to increase yield and cannabinoid concentration of medical cannabis, but increased legalization has heightened awareness of the environmental impact of overfertilization. Elevated levels of phosphorus (P) are of particular concern. Here we report the effects of increasing P above levels adequate for other crops (15, 30, 45, 60, or 90 mg per L) and the interactive effects of elevated P with elevated nutrient solution concentration (electrical conductivity; 2 and 4 mS per cm). We used closed-system hydroponics to continuously quantify rootzone nutrient concentrations. The concentration of P in leaf tissue doubled and flower P concentration increased 70% when the P input increased from 15 to 90 mg per L but there was no difference in yield or quality among treatments. Doubling nutrient input from 2 to 4 mS per cm increased nutrient accumulation in solution but did not significantly increase yield or quality. Reducing P in the refill solution from 90 to 15 mg per L reduced P in solution at harvest from 300 to less than 0.1 mg per L. Despite the low steady-state concentration of P in solution in the 15 mg per L treatment, there was no difference in yield or quality among treatments, regardless of the concentration of other elements. Despite the high nutrient concentrations in the rootzone solution there was no leaf necrosis or other visual effects among treatments. These data indicate cannabis tolerates high nutrient concentrations, but neither excessive P nor excessive fertilization improves yield or quality.